A profile of sexually active male adolescent high school students in Lima, Peru Perfil de los adolescentes varones sexualmente activos en colegios secundarios de Lima, Peru - Jesús L. Chirinos; Victor C. Salazar; Claire D. Brindis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
To document knowledge and attitudes regarding sexuality and sexual practices of male adolescent high school students in Lima, Peru, a self-administered, anonymous survey was completed by 991 male adolescents aged 12-19 as part of a School-Based Sex Education Intervention model. Questions concerned sociodemographic information; family characteristics; personal activities; knowledge and attitudes regarding sexuality; sexual experience; and contraceptive use. Knowledge related to sexuality was limited. Males tended to mainly discuss sexuality with their male peers (49.8%). Attitudes towards sexual activity and condom use were largely positive, although some males expressed ambivalent feelings towards the latter. Of the sample, 43% had ever had sex; age at first sexual intercourse was 13 years. While 88% of the sample would use condoms, 74% also gave reasons for not using them. Sexual activity was related to age, ever having repeated a grade, living with only one parent or in a mixed family, activities such as going to parties, use of alcohol, tobacco, and drugs, and viewing pornographic videos or magazines. Many male adolescents were at risk of causing an unintended pregnancy or acquiring an STD. Con el objetivo de documentar el nivel de conocimiento y las actitudes con respecto a sexualidad y las prácticas sexuales de los adolescentes varones de colegios secundarios en Lima, Peru, 991 estudiantes varones, entre los 12-19 años, completaron una encuesta autoaplicable y anónima dentro de un Programa de Prevención de Comportamientos Sexuales de Riesgo. Datos de la encuesta: sociodemográficos de la familia; de actividades personales; de conocimiento y actitudes con respecto a la sexualidad; de experiencia sexual y uso de anticonceptivos. El conocimiento sobre sexualidad es limitado. Los varones discuten principalmente sobre sexualidad con sus pares varones (49,8%). Las actitudes hacia la actividad sexual y el uso de condones fueron positivas, pero algunos expresaron sentimientos ambivalentes en cuanto a su uso. El 43% había tenido relaciones coitales alguna vez y la edad promedio del inicio sexual fue de 13 años. Mientras que el 88% de la muestra usaría condones, el 74% también dio razones para no usarlos. La actividad sexual se asoció a la edad, a haber repetido un grado, a vivir con uno de los padres o con una familia re-estructurada, con actividades como ir a fiestas, uso de alcohol, tabaco y drogas, y ver revistas o videos pornográficos. Muchos de los adolescentes varones estuvieron en riesgo de ocasionar un embarazo no planeado o adquirir una ETS.